Pemanfaatan AI dalam Pembelajaran Bahasa Indonesia Menurut Siswa SMKN 2 Pengasih - Frandika, Edo; Sisilia, Novianti; Fahrudin, Saleh (Peneliti.net, 2026)
This study aims to analyze the influence of ChatGPT usage on the academic and social activities of students at SMK Negeri 2 Pengasih. The method used in this research is descriptive quantitative with data collection techniques through a survey filled out by 103 students. The collected data were analyzed using descriptive statistics to see the frequency and distribution of respondents' answers. The results show that the majority of students routinely use ChatGPT for academic purposes, especially in finding information and references, which is considered effective in improving the quality and speed of learning. However, the influence of ChatGPT on students' social activities is not significant; most students rarely use it for communication and do not feel a major change in direct social interaction. There were also concerns about the potential for dependence on this technology. The conclusion of this study is that ChatGPT has become a dominant and useful tool in the academic field for vocational school students, but its use in a social context is still limited and there needs to be an awareness of the risk of dependency.